Technological Innovation of the Crypto-Asset Financial Sector in Indonesia after Law Number 4 of 2023 Concerning the Development and Strengthening of the Financial Sector - Izmi, Nurul; Siagian, Abdhy Walid (The International Journal of Financial Systems, 2024)
Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (UUP2SK) has provided changes to all regulatory and supervisory authorities over the operationalisation of cryptocurrencies, which were previously in the hands of the Commodity Futures Trading Supervisory Agency (Bappebti) to the jurisdiction of the Financial Services Authority (OJK). After the enactment of UUP2SK, the authority to regulate and supervise crypto assets is now under the purview of OJK, with the transition of taking over all responsibilities related to crypto assets, but there is no regulation that regulates in detail the procedures for the transfer of authority.